Georges de La Tour and the Enigma of the Visible - Judovitz, Dalia (Book collections on Project MUSE., 2018)
This interdisciplinary study explores George de La Tour's (1593-1652) enigmatic representations of light, vision and the visible in order to question the nature of painting and its religious, artistic and conceptual aspects. Challenging the familiarity of vision, it proposes a spiritual understanding of painting and its engagements with the world.